Strategie rozwoju nauki i szkół wyższych do roku 2020 i dyskusja o reformie szkolnictwa wyższego w Polsce 2008-2011 = Strategies for the development of science and universities to 2020 and discussion on higher education reform in Poland (2008-2011) - Narkiewicz-Niedbalec, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author presented the history of Higher Education Reform in Poland for the years 2008-2011 and the discussion (taking place mainly in the press - "Forum Akademickie", "Gazeta Wyborcza") on the condition of Polish science and the reform. First she showed the changes at Polish universities after 1989, financial condition of universities, the genesis of changes prepared since 2008 and various phenomena within the higher education in Europe, especially massification of education.
Keywords: szkolnictwo wyższe; strategia rozwoju; reformy szkolne; Polska